KONTRIBUSI BIMBINGAN KARIER DAN PRAKTIK KERJA INDUSTRI TERHADAP KESIAPAN KERJA SISWA - Nanang Aria Sandika (EDU RESEARCH, 2024)
This research was conducted as the students have different level of readiness to work. Career guidance and industrial work practice were assumed as the factors exerting influences upon the students’ readiness to work. This research was intended to describe: (1) career guidance, (2) industrial work practice, (3) the students’ readiness to work, (4) the contribution of career guidance toward the students’ readiness to work, (5) the contribution of industrial work practice toward the students’ readiness to work, and (6) the contribution of career guidance and industrial work practice simultaneously toward the students’ readiness to work. This correlational descriptive research applied quantitative method. The population of the research was 292 students in class XII of SMK Negeri 9 Padang. The sample was 169 students which was chosen by using proportional random sampling. To collect the data, Likert scale model was applied. The data obtained were analyzed by using descriptive statistics, simple and multiple regressions. The results of the research indicate that: (1) the average of the career guidance is in good category, (2) the average of the industrial work practice is in good category, (3) the students’ readiness to work is in very ready category, (4) career guidance significantly contributes to the students’ readiness to work, (5) industrial work practice significantly contributes to the students’ readiness to work, and (6) career guidance and industrial work practice simultaneously gives significant contribution to the students’ readiness to work.